Antioxidant Effect of Beta-glucan Extract from Saccharomyces Cerevisiae - Hiba K. Ibrahim1 , Mayaada S. Mahdi1 , Biologist/ Afnan A.2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Natural compound extracted from microorganism is one of the important compound used for treatmentmany diseases in the world ? -glucan is one of these compound that extracted from yeast Saccharomycescerevisiae by acid alkaline method used by Biron. The glucan was analyzed by FTIR ,HPLC, molecularweight was determined and antioxidant effect of ? -glucan was tested . The result showed high compatibilitybetween the sample of glucan and the standard by FTIR, ? -glucan showed high purity of extraction ascompared with standard of glucan by using HPLC.